Natural disasters and teachers’ well-being: An intervention model for improving the occupational well-being of teachers in a post-disaster situation - Baig, Sharifullah; Shafa, Mola Dad; Begum, Abida (ASEAN Natural Disaster Mitigation and Education Journal, 2025)
Background: In disaster situations the hardships and adversities for teachers are amplified because their work is drastically deviated from their normal routine and are expected to take the additional role of socio-psychological guide for the communities, exerting mounting pressure on their professional responsibilities and their well-being. Methods: Therefore, a small-scale intervention was carried out to help the teachers to improve their well-being in a post-disaster situation for two years. Alongside this intervention, a longitudinal qualitative study was carried out to measure the changes in the well-being of the targeted five teachers over a period of two years in a remote, isolated context. The data was collected in three rounds. Round one was carried out at the start, followed by round two in the middle of the intervention, and the final round of data collection was carried out at the end of the study. This study employed the OECD’s tool for measuring the occupational well-being of the teachers. Findings: The study found a gradual and consistent improvement in the cognitive, subjective and social well-being of the teachers. However, satisfaction with profession reflects a stable level of discontent about their career choice and the data suggests that there is a certain level of regret for career choice. In the dimension of physical and mental well-being, the data suggests that participants are facing a variety of physical and emotional symptoms like headache, back pain, stomach pain, feeling nervous, irritability, and sleep deprivation. Conclusions: Teachers must be trained and prepared for an expanded role of leadership in remote contexts not only for education in emergencies but also for community cohesion and well-being in post-disaster situations. Therefore, aid organizations must prioritize the well-being of teachers in post-disaster situations. Novelty/Originality of this article: A small-scale longitudinal qualitative study over two years measuring cognitive, subjective, social, physical, and mental well-being changes of teachers in a remote, isolated post-disaster context using the OECD’s occupational well-being tool.